2021
DOI: 10.3390/cancers13112819
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Angiogenic Treatment in Pseudomyxoma Peritonei—Still a Strong Preclinical Rationale

Abstract: Pseudomyxoma peritonei (PMP) is a rare, slow-growing cancer characterized by progressive accumulation of intraperitoneal mucinous tumor deposits. Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) cures approximately 50% of patients, but in unresectable and recurrent cases, treatment options are limited. Anti-angiogenic treatment is being explored as a potential therapeutic option. Using PMP patient samples, microvessel densities (immunostaining for CD31 and CD105) and pro-angiogenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“… 74 Compared with healthy population, higher expression of angiogenic signaling pathway protein were detected in PMP serum specimens, like VEGFA, PIGF, FGF2, and sflt1. 74 The synergistic action could promote the vascularization. Cases of apatinib treatment, trifluridine/tipiracil (TAS-102) plus bevacizumab and other protocols all have reported with prolonged PFS and improved life quality.…”
Section: Attempts For Progressive Stagementioning
confidence: 93%
See 2 more Smart Citations
“… 74 Compared with healthy population, higher expression of angiogenic signaling pathway protein were detected in PMP serum specimens, like VEGFA, PIGF, FGF2, and sflt1. 74 The synergistic action could promote the vascularization. Cases of apatinib treatment, trifluridine/tipiracil (TAS-102) plus bevacizumab and other protocols all have reported with prolonged PFS and improved life quality.…”
Section: Attempts For Progressive Stagementioning
confidence: 93%
“…PMP lacks in epithelial tumor cells and riches in mucin, that character does not influence the degree of vascularization and bears slight difference with other solid neoplasms 74. Compared with healthy population, higher expression of angiogenic signaling pathway protein were detected in PMP serum specimens, like VEGFA, PIGF, FGF2, and sflt1 74. The synergistic action could promote the vascularization.…”
Section: Attempts For Progressive Stagementioning
confidence: 97%
See 1 more Smart Citation
“…Due to the small number of tumor cells and the large amount of mucus associated with PMP, ordinary conventional chemotherapy drugs cannot play an effective role. Relevant studies have shown that antiangiogenic therapy may be an effective treatment [155,156]. Dohan et al [156] confirmed the existence of a large number of microvessels in PMP tumor tissue through Doppler ultrasound and microangiography.…”
Section: Antiangiogenic Therapymentioning
confidence: 98%
“…In preclinical models of PMP, tumor tissues were found to be vascularized and enriched in relevant pro-angiogenic factors associated with VEGF signaling, and inhibitors of this pathway, such as bevacizumab, were able to interfere with tumor growth in murine PMP xenografts [ 46 ]. Similarly, intraperitoneal administration of bevacizumab in an orthotopic murine model of PMP is correlated with the normalization of tumor vascularity, confirming the potential activity of anti-VEGF target therapy in PMP [ 47 ].…”
Section: Systemic Treatmentsmentioning
confidence: 99%